Fertilizer Response of Eucalyptus tereticornis Seedlings - Prasad, K. G.; Rawat, V. R. S. (Indian Forester, 1994)
Four pot culture experiments were carried out to determine the response of N, P and K by Eucalyptus tereticornis varieties FRI-4 and FRI-5 grown on sandy loam New Forest Soils, Leaf number, average leaf area, total leaf area, fresh biomass and dry biomass of both the varieties responded to N application whereas variety FRI-4 responded to N+K application and variety FRI-5 to N+P application. These growth parameters were also highly correlated with the Fertilizer Use Efficiency (FUE) (mg dry biomass/mg N, P or K). Interestingly FUE of varieties FRI-4 and 5 were inherited from their mothers E. camaldulensis and E. tereticornis respectively. Further, these parameters were directly related to the relative chlorophyll content of leaves; a determination of light transmission through leaf at photographic infrared band; measured using "Agrophotometer".